👤

Aflați rezultatul calcului [0,4minus 0,0 (6)]la a2÷1, (3)

Răspuns :

Răspuns:

[0,4minus 0,0 (6)]la a2÷1, (3)] =

[0,4-0,0(6)] ^2 :1,(3)=

(4/10-6/90)^2: 12/9=

Aducem paranteza la același numitor

(36/90-6/90)^2 : 12/9=

(30/90)^2 : 12/9=

(1/3)^2×9/12=

1/9× 9/12=

1/12

Explicație pas cu pas:

Răspuns:

Explicație pas cu pas:

[tex]\frac{(0,4-0,0(6))^{2} }{1,(3)} =\frac{(\frac{4}{10}-\frac{6}{90} )^{2} }{\frac{12}{9} }=(\frac{1}{3}) ^{2} *\frac{3}{4} =\frac{1}{9}*\frac{3}{4} =\frac{1}{12}[/tex]